Network pharmacology and experimental validation to elucidate the pharmacological mechanisms of Guben Xiezhuo decoction against renal fibrosis - Shutao Chen; Yue Liu; Liwei Zhu; Jingyi Wu; Ziyun Xu; Yingyu Zhang; Minggang Wei; Zhenfang Du; Sheng Qiang (Scientific Reports)
Abstract Guben Xiezhuo decoction (GBXZD), a traditional Chinese medicine (TCM), shows promise in treating chronic kidney disease (CKD) by reducing renal fibrosis (RF). This study seeks to uncover the exact mechanism behind GBXZD’s therapeutic effects. This study identified 14 active components and 18 specific metabolites in the serum of GBXZD-treated rats via mass spectrometry. Potential target proteins were predicted using PubChem, TCMSP, and SwissTargetPrediction databases and refined through OMIM and Genecards databases. A total of 276 proteins were filtered from these potential target proteins to develop a protein-protein interaction (PPI) network to explore the interactions between GBXZD and RF target proteins, revealing significant correlations for proteins such as SRC, EGFR, and MAPK3. Subsequently, the active components and specific metabolites were employed for molecule docking simulation to assess their interactions with EGFR protein. The effects and mechanisms of GBXZD on RF were validated in a unilateral ureteral obstruction (UUO) rat model by assessing changes in RF-related protein expressions identified from the PPI network. GBXZD showed a reduction in the phosphorylation expression of SRC, EGFR, ERK1, JNK, and STAT3. In vitro, LPS stimulated HK 2 cells treated with the identified GBXZD bioactive components trans-3-Indoleacrylic acid and Cuminaldehyde exhibited significantly enhanced viability and reduced fibrotic marker expression and p-EGFR levels. KEGG pathway analysis suggested that GBXZD’s anti-fibrotic effects might be mediated by inhibiting the EGFR tyrosine kinase inhibitor resistance and MAPK signaling pathways.